Review Makanan Kaya Lemak Pada Kontrol Obesitas melalui Penghambatan Induksi Enzim - Desi Ratna Sari; Aurelia Afra; Erni Yupita Sari Br Sembiring; Cico Jhon Karunia Simamora (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: Obesity is an imbalance between height and weight due to excessive body fat tissue. The purpose of writing this review is to find out the effect of enzyme inhibitor induction on fat-rich foods as control of obesity. Method: Writing and assessing source problems related to using literature study methods. Results: One way of controlling obesity is by regulating dietary patterns and consumption of lipase inhibitors. Inhibition of lipase is one of the most widely developed effective ways in diet medicine. Inhibitory compounds cause pancreatic lipase to lose its ability in decomposition that enters the blood. The potency of plant-origin lipase inhibitor compounds can be increased in both number and performance. Increasing the production of secondary metabolite group inhibitors is by fermentation of microorganisms. Conclusion: Inhibition of triglyceride hydrolysis through inhibition of lipase enzymes can decrease and prevent obesity. Secondary metabolite induction can be fermented with microorganisms. The production of secondary metabolite compounds in medicinal plants can be increased in the presence of fermentation. Flavonoids can decrease the accumulation of lipids in the heart, reduce glucose absorption, inhibit the breakdown of polysaccharides into monosaccharides.